Higher cigarette taxes--healthier people, wealthier state: the Hungarian experience - Szilágyi, Tibor (Central European journal of public health, 2007)
OBJECTIVE: To prove that higher cigarette taxes eventually decrease smoking and do also increase state incomes from tobacco taxes by using Hungarian figures. METHOD: Collection and analysis of available data on tobacco use, levels of excise and value added taxes on tobacco products and state incomes originating from the tobacco sector. CONCLUSIONS: In Hungary, regular tobacco tax increases resulted in decreased cigarette consumption and its lower prevalence figures in some population groups. State incomes have increased in spite of regular cigarette tax raises. Therefore, there is on conflict of interest between the health and finance portfolios in supporting further tobacco tax increases. Hungary should use regular, above the inflation tobacco tax raises as means for improving population health. Tobacco control advocates should prevent tobacco companies' attempts aimed at deterring decision makers from supporting such tax policies.
Keywords: Hungary; Taxes; věkové faktory; prevalence; lidé; zdravotní stav; Health Status; Models, Econometric; příjem; Maďarsko; Prevalence; tabák; Age Factors; daně; ekonometrické modely; Income; Tobacco Products; Humans